Penegakan Hukum Terhadap Pelanggaran Kode Etik Advokat - Giovani D.B. Nggabut; Adean E. Berti Bano; Damianus Bria; Kathrine M. Mamengko; Yuliiyana C.S. Mudamakin (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
Based on Article 33 of Law Number 18 of 2003 concerning Advocates, this code of ethics is declared mutatis mutandis to be valid until new provisions are made by the advocate organization. Considering that in Article 16 of Law Number 18 of 2003 concerning Advocates in conjunction with Constitutional Court decision No. 26/PUU-XI/2013 concerning Advocates, it is stated that: "Advocates cannot be prosecuted either civilly or criminally for carrying out their professional duties in good faith for the benefit of client defense inside and outside the courtroom." In this article, advocates in carrying out their profession, apart from being guaranteed by law normatively, also have the right to immunity or impunity in carrying out their profession by adhering to the professional code of ethics. However, what is in focus here is what kind of good faith is meant in the Article, because the good faith meant in the Article has a very broad or general meaning where the advocate's right to immunity depends on the good faith of the advocate. This gives rise to vague norms that arise in society and this is clearly in conflict with the principle of legal certainty where there should be no conflicting laws and laws must also be made with formulations that can be understood by the general public. Problem formulation: How is law enforcement against violations of the code of ethics committed by advocates. The method used in this research is a normative juridical approach, or library legal research, namely legal research carried out by examining library materials or secondary data. In carrying out their duties, advocates need to fulfill the limitations specified in Law Number 18 of 2003 concerning Advocates. Apart from the Law, advocates also have a Code of Ethics which imposes obligations and at the same time provides legal protection to each member in carrying out their profession. In order for a professional code of ethics to function properly and effectively, there must be a body or instrument tasked with developing and supervising it. In advocate organizations, it is usually assigned to a body or professional honorary council to carry it out. Apart from ensuring that the rules of the code of ethics are obeyed by all members, this body also has the authority to carry out discipline or administrative action against its members who clearly violate the professional code of ethics. The administrative action taken by the honorary council can be in the form of the lightest punishment, for example in the form of a reprimand or warning, but it is possible that considering and considering the seriousness of the code of ethics violations committed by its members, the honorary council may impose severe punishment in the form of dismissal from membership in the organization. Advocate is a noble and honorable profession (Officium Nobile). In accordance with Article 5 paragraph (1) of Law Number 18 of 2003 concerning Advocates, Advocates are also law enforcers in Indonesia apart from Judges, Prosecutors and Police. If an advocate violates the code of ethics, he will receive a warning or warning and light sanctions in the form of administrative sanctions and heavy sanctions in the form of dismissal from membership. Advocates are free to express opinions or statements in defending cases for which they are responsible in court by adhering to the professional code of ethics and statutory regulations. In carrying out their profession, Advocates have the right to obtain information, data and other documents, both from government agencies and other parties related to these interests which are necessary to defend the Client's interests in accordance with statutory regulations.